687 Enhancement of anti-tumor immunity by ICT01: a novel g9d2 T cell-activating antibody targeting butyrophilin-3A (BTN3A). (9th November 2020) - Gassart, Aude de; Brune, Patrick; Suong, LE; Agaugue, Sophie; Valentin, Emmanuel; Castellano, Remy; Sims, Jennifer; Truneh, Alem; Olive, Daniel; Hoet, Rene
Abstract : Background: gdT-cells are innate-like lymphocytes described as potent killer of cancer cells whose infiltration into tumors is associated with a positive prognosis. 1 2 This supports gd T-cells use in cancer immunotherapy. BTN3A, which belongs to the B7-subfamily of Ig proteins, is required for the recognition of malignant or infected cells by human g9d2 T-cells by sensing intracellular accumulation of phosphoantigens. 3 ImCheck Therapeutics is developing ICT01, a humanized anti-BTN3A (IgG1, Fc-silenced), g9d2 T-cell-activating antibody for the treatment of patients with solid or hematologic tumors. Methods: A complete IND-enabling program was conducted to characterize the preclinical activity and safety of ICT01. ICT01 effects on human and cynomolgus PBMCs were characterized in vitro using flow cytometry. ICT01-mediated killing activity of g9d2 T-cells was assessed using in vitro co-cultures with tumor and non-tumor cells. Immunocompromised mice bearing human tumors and adoptively transferred with human g9d2 T cells were used to assess ICT01 anti-tumor activity in vivo. The PK, PD and safety of intravenous ICT01 (0.1 to 100 mg/kg single- and repeated-dose) were evaluated in Cynomolgus monkeys. Results: ICT01 selectively binds to all three BTN3A isoforms with high affinity (<10nM). When assayed in human and cynomolgus PBMCs in vitro, ICT01 promoted a robust and specific activation of g9d2 T-cells as shown by concentration dependent increase in cell surface CD69 and CD25 and cytokines secretion (IFNγ, TNFα). In co-culture experiments, 20% of target occupancy on tumor cells is sufficient for maximal g9d2 T-cell degranulation (e.g. CD107a/b expression). ICT01-activated g9d2 T-cells continuously and serially kill a wide range of tumor cells in multi-day co-culture conditions. In contrast, non-tumoral BTN3A-expressing B cells, HUVEC and fibroblasts were unaffected. In mouse AML and ovarian cancer models, repeated injections of ICT01 delayed tumor growth and significantly prolonged animal survival. In primates, ICT01 exposure and target engagement was dose-dependent, with all tested doses producing a specific g9d2 T cell activation and trafficking out of the circulation within 1 hour. ICT01 administration was well tolerated with no safety signals observed at doses up to 25 mg/kg/week based on clinical, laboratory, and anatomic pathology parameters. Conclusions: The combined in vitro and in vivo pharmacology data provide evidence that ICT01 is an attractive and novel therapeutic approach for enhancing the innate anti-tumor potential of g9d2 T-cells by activating BTN3A. Importantly, ICT01 did not affect healthy BTN3A-expressing cells, and NHP studies confirmed ICT01 safety with a wide therapeutic index. Therefore, ICT01 is being tested in the ongoing EVICTION trial (NCT04243499 ). Ethics Approval: Pseudonymized samples isolated from healthy volunteers' whole blood by ImCheck Therapeutics under the agreement n° 7173 between ImCheck Therapeutic SAS and EFS PACA (Etablissement Français du Sang Provence-Alpes-cote d'Azur) References: Gentles AJ, Newman AM, Liu CL, et al. The prognostic landscape of genes and infiltrating immune cells across human cancers. Nature Medicine 2015;21(8):938–945. Tosolini M, Pont F, Poupot M, et al. Assessment of tumor-infiltrating TCRVγ9Vδ2 γδ lymphocyte abundance by deconvolution of human cancers microarrays. OncoImmunology . 2017;6(3):e1284723. Harly C, Guillaume Y, Nedellec S, et al. Key implication of CD277/butyrophilin-3 (BTN3A) in cellular stress sensing by a major human γδ T-cell subset. Blood 2012;120(11):2269–2279.